Caries experience after periodontal treatment in aggressive and chronic periodontitis: Results of a 10-year follow-up. (September 2013) - Meyer-Bäumer, Amelie; Eickholz, Peter; Reitmeir, Peter; Staehle, Hans Jörg; Frese, Cornelia; Wohlrab, Theresa; Pretzl, Bernadette
Abstract: Objective. To compare the increase of DMF-T and DMF-S in patients with aggressive periodontitis (AgP) and chronic periodontitis (ChP) after active periodontal therapy. Materials and methods. One hundred and thirty-six periodontally treated patients were re-examined after 10 years. Dental and periodontal status was assessed and patients' charts were screened for diagnosis, compliance to supportive periodontal treatment (SPT) and DMF-T/-S at baseline and re-examination. δDMF-T/-S was calculated and multi-level regression analyses were performed to identify factors contributing to increase of DMF-T/-S. Results. Thirty patients with AgP, 37 with moderate ChP and 69 with severe ChP could be included. δDMF-T between first visit and re-examination was 2.07 (SD = 2.51, range = 0–14 teeth), mean δDMF-S = 14.66 (SD = 14.54, range = 0–83 surfaces). Patients with AgP showed a similar increase in DMF-T/-S to those with ChP. Regression analysis identified compliance as the only factor significantly accounting for preventing an increase of DMF-S ( p = 0.017). No factor had a significant impact on DMF-T. Conclusions. DMF-T and DMF-S developed similarly in periodontally-treated patients with AgP and ChP during a follow-up of 10 years. SPT showed a positive influence on avoiding decline in DMF-S in periodontally compromised patients. No significant impact was detected for all other studied factors.